Is it possible to use additive manufacturing for accelerator UHV beam pipes?. (November 2019) - Jenzer, S.; Alves, M.; Bilgen, S.; Bonis, J.; Brisset, F.; Djelali, S.; Gonnin, A.; Guerrier, M.; Grasset, D.; Letellier-Cohen, F.; Mercier, B.; Mistretta, E.; et al.
Abstract: Additive Manufacturing (AM) enables 3D metallic objects to be built by adding layer- upon-layer of material. This technology can be applied to produce Ultra High Vacuum components for particle accelerators. We investigated in this work the reproducibility of AM 316L stainless steel properties for different specimens supplied by several manufacturers with the same process. Microstructure and mechanical properties of AM samples depends on manufacturers: indeed, they are largely influenced by processing parameters, which produces heterogeneous and anisotropic microstructures that differ from traditional wrought counterparts. The outgassing rates of vacuum AM 316L tubes were determined and the secondary electron yield was also measured. Results are very promising to consider the use of AM to construct accelerator beam pipe components.